METABOLITES PROFILE OF COLORECTAL CANCER CELLS AT DIFFERENT STAGES - YUSOF, HAZWANI MOHD; AB-RAHIM, SHARANIZA; WAN NGAH, WAN ZURINAH; NATHAN, SHEILA; JAMAL A., RAHMAN A.; MAZLAN, MUSALMAH (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study is to characterize the metabolite profiles of colorectal cancer (CRC) cells of different stages of the disease to understand the pathophysiological changes that may help to identify prevention strategies as well as the sites for potential therapeutic drug actions. Methods: Six CRC cell lines of different stages (classified using the Dukes classification) were used, and they are SW 1116 (stage A), HT 29 and SW 480 (stage B), HCT 15 and DLD-1 (stage C), and HCT 116 (stage D). Metabolites were extracted using methanol and water, and metabolic profiling was performed using liquid chromatography-mass spectrometry. Mass profiler professional software was used for statistical analysis. Results: There were 111,096 compounds detected across the samples, and 24 metabolites were identified to be significantly different between the CRC stages. Most notably, there were eight metabolites that were significantly upregulated in the more advanced stages (B, C, and D) compared with Stage A. These metabolites include flavin mononucleotide, l-methionine, muricatacin, amillaripin, 2-methylbutyroylcarnitine, lumichrome, hexadeconoic acid, and lysoPE (0:0/16:0). Conclusion: This study showed that the expressions of metabolites at different stages of CRC were different, which represent the metabolic changes occurring as CRC advances. The knowledge may help identify biomarkers for the staging of CRC, which could improve its prognosis as well as provide a basis for the development of therapeutic interventions.